Are the Millennium Development Goals achievable? (2004)
Presents arguments on whether the Millennium Development Goals are achievable. Suggests that they are achievable but participants to the conference differ on how these goals would be achieved.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT